Minimum surgical volume to ensure 5‐year survival probability for six cancer sites in Japan - Sumiyo Okawa; Takahiro Tabuchi; Toshitaka Morishima; Kayo Nakata; Shihoko Koyama; Satomi Odani; Isao Miyashiro (Cancer Medicine, 2023)
Abstract Background In Japan, the government designates hospitals specialized in cancer care, requiring them to perform 400 surgeries annually without requiring surgical volume per cancer site. This study aimed to estimate the site‐specific minimum surgical volume per year based on its associations with 5‐year survival probability. Methods The data of 64,402 patients who had undergone surgery for six types of cancers (including esophageal, stomach, colorectal, pancreatic, lung, and breast cancers) at designated cancer care hospitals in Osaka between 2007 and 2011 were analyzed. The hospitals were categorized by the average annual surgical volume per cancer type (e.g., 0–4, 5–9, 10–14…). We estimated the adjusted 5‐year survival probability per surgical volume category using multivariable Cox proportional hazard regression. Furthermore, we identified inflection points for the trend of adjusted survival probability per increase of five surgical volumes using the joinpoint regression model and considered them as the suggested minimum surgical volume. Results The estimated minimum surgical volumes were 35–39, 20–25, 25–29, 10–14, 10–14, and 25–29 for esophageal, stomach, colorectal, pancreatic, lung, and breast cancers, respectively. The percentage change in the adjusted 5‐year survival probability per increase of five surgical volumes before and after the suggested surgical volume were +2.23 and +0.39 for the esophagus, +9.68 and +0.34 for the stomach, +8.11 and +0.05 for the colorectum, +3.82 and +0.87 for the pancreas, +9.46 and +0.23 for the lung, and +1.27 and +0.03 for the breast. Conclusions The suggested surgical volume based on the association with survival probability varies with cancer sites, some of which are close to the existing surgical volume standards used in Japan. These evidence‐based minimum surgical volumes may help improve the quality of cancer surgeries.